2016
DOI: 10.30858/zer/83059
|View full text |Cite
|
Sign up to set email alerts
|

Czynniki Wartości Ziemi Rolnej W Kontekście Zróżnicowanych Funkcji Obszarów Wiejskich W Polsce

Abstract: According to many researches, decoupled CAP subsidies capitalised on land prices. Most studies on land prices carried out in Europe relate to the sPs system and marginal changes in land values are noted as a result of the subsidising of agriculture. in the saPs system, used in the new eU-12 Member states, these issues have not been sufficiently investigated. an attempt is made to fill these gaps by studying the drivers of land values in a leading agricultural region of Poland based on a sample of 653 transacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…8. External factors -the implementation of the Common Agricultural Policy contributes to changes in the area structure of agricultural holdings and significantly affects the increase in the price of agricultural real estate (Czyżewski and Trojanek, 2016). In the context of the European agricultural policy, the range of factors influencing the obtained transaction prices of sold agricultural real estate has also expanded (Foryś and Putek-Szeląg, 2008).…”
Section: Attributes Of Attractiveness Shaping Prices and Values Of Ag...mentioning
confidence: 99%
“…8. External factors -the implementation of the Common Agricultural Policy contributes to changes in the area structure of agricultural holdings and significantly affects the increase in the price of agricultural real estate (Czyżewski and Trojanek, 2016). In the context of the European agricultural policy, the range of factors influencing the obtained transaction prices of sold agricultural real estate has also expanded (Foryś and Putek-Szeląg, 2008).…”
Section: Attributes Of Attractiveness Shaping Prices and Values Of Ag...mentioning
confidence: 99%
“…Identification of properties influencing the agricultural land prices in Turkey showed that, with the use of a similar modelling, distance from the farm, organic matter, potassium, water saturation, pH, salinity, phosphate, easement values are statistically significant (Vural and Fidan, 2009). Newer research, implemented by Czyżewski and Trojanek (2016), assigned key significance to the location factor termed "functional…”
Section: Valorisation Of Agricultural Land -Input Income and Hedonicmentioning
confidence: 99%